Plant Bioactive Compounds in Pre- and Postharvest Management for Aflatoxins Reduction - Loi, Martina; Paciolla, Costantino; Logrieco, Antonio F.; Mulè, Giuseppina (Frontiers in Microbiology, 2020)
Aflatoxins (AFs) are secondary metabolites produced by Aspergillus spp., known for their hepatotoxic, carcinogenic and mutagenic activity in humans and animals. AFs contamination of staple food commodities is a global concern, due to their toxicity, and the economic losses they cause. Different strategies have been applied to reduce fungal contamination and AFs production. Among them, the use of natural, plant derived compounds is emerging as a promising strategy to be applied to control both Aspergillus spoilage and AFs contamination in food and feed commodities in an integrated pre and post-harvest management. In particular, phenols, aldehydes, and terpenes extracted from medicinal plants, spices, or fruits have been studied in depth. They can be easily extracted, they are Generally Recognized As Safe (GRAS), they are food-grade and act through a wide variety of mechanisms. This review investigated the main compounds with antifungal and anti- aflatoxigenic activity, also elucidating their physiological role, the different modes of action and synergies. Plant bioactive compounds shown to be effective in modulating Aspergillus spp. contamination and AFs production both in vitro and in vivo. Therefore, their application in pre and post-harvest management could represent an important tool to control aflatoxigenic fungi and to reduce AFs contamination.